Collaborative and secure transmission of medical data applied to mobile healthcare - Weimin Chen (BioMedical Engineering OnLine, 2019)
Abstract Purpose We propose a collaborative and secure transmission scheme in order to safely and efficiently transmit medical data and provide telemedicine services, lighten the load on wireless access networks, and improve the quality of medical treatment such as surgery. Methods First, the transmission technology based on opportunistic networks is used to upload patient physiological data and share medical information. Second, we propose a trusted transfer scheme based on the circle of friends, which is constructed with historical encounters and social features of nodes. This scheme takes the forwarding policy of each packet by close friends to effectively prevent the participation of strangers, and avoid privacy issues and deal with selfish behaviors. At the same time, the structure of friend circle is beneficial to the improvement of medical data transmission. Third, we present a lossless compression scheme with less computation and higher compression ratio to reduce the amount of medical data and improve the performance of the transmission. Results The experimental results show that the proposed scheme is effective and has good transmission performance while ensuring the safety and reliability of media data. Conclusion The mobile healthcare faces some challenges such as the vastness of medical data and sensitivity of patient information. Using opportunistic networks to transmit medical data in mobile healthcare is a good solution, which can effectively divert and offload the data traffic of mobile Internet. The structure of friend circles and the technology of data compression are beneficial to safely and efficiently transmit the patient’s physiological parameters and medical health information.